Venturi pump-critical orifice as an online and robust nanoparticle dilution probe for in situ powder stream characterization - Vazquez-Pufleau, Miguel (Powder technology, 2022)
The study of aerosol dynamics in nanomaterial synthesis and powder processing requires real time, fast, automatic and reliable characterization of particle size distribution and concentration. Online characterization techniques, such as the scanning mobility particle sizer (SMPS) allow these measurements for aerosol systems. Unfortunately, the SMPS was developed and optimized primarily for atmospheric sampling. However, reactors for the purposeful synthesis of nanoparticles operate in highly dynamic conditions with high concentrations, various pressures and even flammable, pyrophoric or toxic gases, demanding fast and reliable quenching, diluting and transporting the aerosols towards characterization. In the present work, a sampling and dilution probe based on the Venturi principle with different orifice sizes was characterized using polystyrene latex beads and salt. The obtained dilution rates were compared vs state of the art equations and precursor dilution from a silane reactor showing good agreement. The smallest orifices could clog but ethanol and pressurized gas allow their regeneration. [Display omitted] •Study compares dilution probe capabilities on PSL beads, salt and silane vs models.•Probes useful for characterizing & monitoring aerosol reactors and generators.•Particularly attractive in systems with toxic, explosive or pyrophoric atmospheres.•Cheap, operational at different pressures, allows quenching fast aerosol dynamics.•Experiments agree with predictions PSL standard shows advantages over salt.